Transcranial random noise stimulation-induced plasticity is NMDA-receptor independent but sodium-channel blocker and benzodiazepines sensitive - Chaieb, Leila; Antal, Andrea; Paulus, Walter (Frontiers in Neuroscience, 2015)
Background: Application of transcranial random noise stimulation (tRNS) between 0.1 and 640 Hz of the primary motor cortex (M1) for 10 minutes induces a persistent excitability increase lasting for at least 60 minutes. However, the mechanism of tRNS-induced cortical excitability alterations is not yet fully understood. Objective: The main aim of this study was to get first efficacy data with regard to the possible neuronal effect of tRNS. Methods: Single-pulse transcranial magnetic stimulation (TMS) was used to measure levels of cortical excitability before and after combined application of tRNS at an intensity of 1mA for 10mins stimulation duration and a pharmacological agent (or sham) on 8 healthy male participants. Results: The sodium channel blocker carbamazepine showed a tendency towards inhibiting MEPs 5-60 mins poststimulation. The GABAA agonist lorazepam suppressed tRNS-induced cortical excitability increases at 0-20 and 60 min time points. The partial NMDA receptor agonist D-cycloserine, the NMDA receptor antagonist dextromethorphan and the D2/D3 receptor agonist ropinirole had no significant effects on the excitability increases seen with tRNS. Conclusions: In contrast to transcranial direct current stimulation (tDCS), aftereffects of tRNS are seem to be not NMDA receptor dependent and can be suppressed by benzodiazepines suggesting that tDCS and tRNS depend upon different mechanisms.